Propriedades de medida do Lower Extremity Motor Coordination Test em indivíduos hemiparéticos - Kenia Kiefer Parreiras de Menezes (2014)
Introduction: In stroke patients, the loss of motor coordination significantly contributes to disabilities. The assessment of motor coordination of the lower limbs is important for the planning, development, and modification of the treatment of these individuals, since adequate motor coordination is essential in many everyday motor activities. The Lower Extremity Motor Coordination Test (LEMOCOT), used to quantitatively evaluate the motor coordination of the lower limbs, is easily administered and understand. Thus, it is necessary to investigate its measurement properties in this population, such as the intra-, inter-rater, and test-retest reliabilities, construct and criterion validities, the best source of obtaining the score, as well as its ability to detect real changes in stroke subjects. Objective: To evaluate the measurement properties and the applicability of LEMOCOT with stroke subjects. Materials and methods: Thirty-six stroke participants, 18 sub-acute and 18 chronic subjects, were divided into three subgroups, according to their functional levels, based upon their gait speed. The following outcome measures were obtained: Motor recovery, sensory information, muscular tone, strength, motor coordination, and gait speed. Results: For the intra-, inter-rater, and test-retest reliabilities, excellent and significant coefficients were found for both the paretic limb and non-paretic lower limbs for the two sub-acute and chronic groups (ICC>0.93, p<0.0001). The standard error of the mean values found for the paretic and non- paretic lower limbs were acceptable (<15%), as well as the minimal detectable change values. ANOVAs revealed significant differences between the various sources of outcome scores for both the paretic (5.08<F<51.41, p<0.01) and non-paretic (18.92<F<82.17, p<0.01) lower limbs, suggesting that the means of three trials should be used. The LEMOCOT was able to discriminate individuals with and without hemiparesis and between the paretic and non-paretic lower limbs for both sub-acute and chronic groups. The LEMOCOT scores were not able to differentiate between individuals with different functional levels and motor recovery. When the LEMOCOT scores were compared between individuals, whose dominance prior to stroke was the dominant side, no significant differences were found (p=0.93). Significant and positive correlations were found between the LEMOCOT scores and measures of strength of the paretic knee flexors and extensors and hip flexors (0.390.56, p=<0.01) and esthesiometry (=0.40, p=0.02). No significant differences were found between the direct and video observations for both limbs (ICC=0.99, p<0.0001). The regression analyses revealed that only motor recovery and tonus of the plantar flexor muscles were able to explain 50% of the variance of the LEMOCOT scores. Conclusions: The findings demonstrated that the LEMOCOT demonstrated adequate measurement properties in stroke subjects and, therefore, could be an appropriate measure for research and clinical purposes. Furthermore, the means of three trials should be used to score the test, either from direct observations or video analyses.